Surface treatment of cellulose fibers with methylmethacrylate for enhanced properties of in situ polymerized PMMA/cellulose composites. Issue 2 (22nd August 2013) - Banerjee, Moloy; Sain, Sunanda; Mukhopadhyay, Anirudhha; Sengupta, Suparna; Kar, Tanusree; Ray, Dipa
ABSTRACT Cellulose micro/nanofibers (CNF), prepared from jute fibers were surface treated with methyl methacrylate (MMA) for better dispersion into poly methyl methacrylate (PMMA) matrix. PMMA/cellulose composites were prepared by in situ suspension polymerization technique. The surface treatment of CNF was confirmed by Fourier transform infrared spectroscopy (FTIR) and Nuclear magnetic resonance (NMR) analysis. MMA‐treated cellulose micro/nanofibers (MCNF) demonstrated improved affinity and dispersion in MMA monomer as well as in the PMMA/cellulose composites. Thermal properties of the cellulose composites were analyzed by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The glass transition temperature (Tg) of PMMA increased by nearly 19°C in the in situ cellulose composites compared to that of unreinforced PMMA as indicated by DSC. TGA showed increased thermal stability of the cellulose composites. Enhanced tensile properties as well as significantly lower moisture uptake were observed in the in situ prepared PMMA/cellulose composites. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39808.